SYSTEMATIC LITERATURE REVIEW: PENGARUH MODEL FLIPPED CLASSROOM BERBANTUAN PLATFORM DIGITAL TERHADAP LITERASI SAINS DAN KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN IPA SEKOLAH DASAR - Kartika Arlianasari Nurrohmah; Mas'ula, Siti; Ekawati, Ratna; Pristiani, Riska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the flipped classroom model assisted by digital platforms on scientific literacy and critical thinking skills in elementary science learning. This research employed a Systematic Literature Review (SLR) method by examining relevant articles published between 2020 and 2026 from databases such as Google Scholar, Scopus, and SINTA. The selection process was conducted based on inclusion criteria related to the application of flipped classroom, scientific literacy, and critical thinking skills at the elementary school level. The results of the study indicate that the flipped classroom model has a positive and significant impact on improving students’ scientific literacy and critical thinking skills. The use of digital platforms, such as instructional videos and online learning media, provides flexibility in learning and enhances students’ independent learning abilities. In addition, classroom learning becomes more meaningful through interactive activities such as discussion, problem-solving, and concept analysis. However, the effectiveness of this model is influenced by factors such as technological access, teacher readiness, and students’ learning motivation. Therefore, the flipped classroom model can be used as an innovative learning strategy to support the development of 21st-century skills in elementary education.